2020
DOI: 10.1021/acscatal.0c04280
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Cross-Coupling of Hindered, Electron-Deficient Anilines with Bulky (Hetero)aryl Halides Using Biaryl Phosphorinane Ligands

Abstract: Biaryl phosphorinane ligands derived from addition of biaryl primary phosphines to trans,trans-dibenzylideneacetone (Alison-Phos and AliPhos) form highly active ligands for Pd-catalyzed coupling of hindered, electron-deficient anilines with hindered (hetero)aryl halides, a challenging class of C−N cross-coupling reaction with few precedents. Broad substrate scope and functional group tolerance were observed under the reaction conditions. Computational studies suggest that ligands containing phenyl substituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…In search of a suitable ligand for a challenging Pd-catalyzed cross-coupling of hindered, electron-deficient anilines with hindered (hetero)­aryl halides, Shekhar and co-workers developed a general strategy for the synthesis of biarylphosphorinanes via a phospha-Michael addition (Scheme ). Solvent screening indicated that HFIP gave the desired phospha-Michael addition product in high yield. The phosphinanones were directly converted to phosphorinanes, which were then screened for their utility as ligands.…”
Section: Heteroatom Additions and Eliminationsmentioning
confidence: 99%
“…In search of a suitable ligand for a challenging Pd-catalyzed cross-coupling of hindered, electron-deficient anilines with hindered (hetero)­aryl halides, Shekhar and co-workers developed a general strategy for the synthesis of biarylphosphorinanes via a phospha-Michael addition (Scheme ). Solvent screening indicated that HFIP gave the desired phospha-Michael addition product in high yield. The phosphinanones were directly converted to phosphorinanes, which were then screened for their utility as ligands.…”
Section: Heteroatom Additions and Eliminationsmentioning
confidence: 99%
“…The orthosubstituted, electron-poor anilines were seldom able to couple with ortho-substituted aryl chlorides, as electron-deficient anilines are poor nucleophiles. 15 Herein, we successfully demonstrated the C−N coupling of sterically hindered 2chloro-3-methylbenzonitrile with 3-fluoro-2-methylaniline using 3.0 mol % Pd loading.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The amination reactions proceeded well with the sterically demanding aryl chlorides with an aniline containing di- o -methyl groups, or even 2,6-diisopropyl substituents, with 1.0 mol % Pd loading. The ortho -substituted, electron-poor anilines were seldom able to couple with ortho -substituted aryl chlorides, as electron-deficient anilines are poor nucleophiles . Herein, we successfully demonstrated the C–N coupling of sterically hindered 2-chloro-3-methylbenzonitrile with 3-fluoro-2-methylaniline using 3.0 mol % Pd loading.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve a high efficiency in this C–N cross-coupling reaction, much attention has been paid to the development of palladium catalysts with new ligands. Until now, a variety of sterically demanding and electron-rich phosphines were designed and synthesized for this purpose, and some of them, such as Buchwald’s and Hartwig’s phosphines, displayed high activities in the amination . Since the first isolation of free N -heterocyclic carbenes (NHCs) by Arduengo, Pd­(II)-NHC precatalysts exhibit much promise in palladium-catalyzed amination thanks to their strong electron donation and the steric protection of the palladium center .…”
mentioning
confidence: 99%